2022
DOI: 10.1002/ps.6788
|View full text |Cite
|
Sign up to set email alerts
|

Miticidal activity of fenazaquin and fenpyroximate againstVarroa destructor, an ectoparasite ofApis mellifera

Abstract: BACKGROUND The Varroa mite (Varroa destructor) is an ectoparasite that can affect the health of honey bees (Apis mellifera) and contributes to the loss of colony productivity. The limited availability of Varroacides with different modes of action in Canada has resulted in the development of chemical resistance in mite populations. Therefore, an urgent need to evaluate new potential miticides that are safe for bees and exhibit high efficacy against Varroa exists. In this study, the acute contact toxicity of 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…Abamectin and Fenpyroximate are broad-spectrum acaricides and insecticides (Hooper-Bui and Rust 2000, Bahreini et al 2022). Abamectin kills insects by increasing the opening of the glutamate-gated chloride channel, causing paralysis and death (Bloomquist 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Abamectin and Fenpyroximate are broad-spectrum acaricides and insecticides (Hooper-Bui and Rust 2000, Bahreini et al 2022). Abamectin kills insects by increasing the opening of the glutamate-gated chloride channel, causing paralysis and death (Bloomquist 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Obtained results of our ongoing research showed that ortus (fenpyroximate) had the least honey bee mortality (less than 30%). Bahreini et al, (2022) mentioned that fenpyroximate (pyrazole class) had lower bee mortality after 24 hrs of treatment. Additionally, both compounds could provide effective Varroa control and alternative options for managing Varroa resistance to be included in current IPM practices, and enable sustainable, productive, and healthy honeybee stocks for the future.…”
Section: Honey Bees Mortalitymentioning
confidence: 99%
“…50 The Apiarium was chosen because it has proven to be a reliable indicator of Varroacide efficacy in the field. 51 It allows bees to express natural behaviors like clustering, and provides opportunities to move away from the Varroacide, similar to a colony environment. It also allows for natural mite drop, avoiding dislodging mites from the bees when shaking at the end of the test, as is done when using the Mason jar method.…”
Section: Introductionmentioning
confidence: 99%